2009
DOI: 10.1111/j.1708-8208.2008.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Changes in the Ultrastructure of Titanium‐Bone Interfaces: Analysis by Light Microscopy, Transmission Electron Microscopy, and Micro‐Computed Tomography

Abstract: Comparative analysis of the titanium-bone interfaces using light microscopy, TEM, and QCT by micro-CT revealed the precise process of osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…Similar observations have been reported in several different TiO 2 dental implant surfaces in in vitro and in vivo rat tibia studies. 11,[35][36][37][38] The proposed mechanism of titanium-associated osteoinduction is thought to be related to hydroxyl groups and calcium ions present in TiO 2 surfaces. These hydroxyl groups may well promote adsorption of calcium-binding extracellular matrix proteins (e.g., alkaline phosphatase) and RGD-specific peptide sequences (e.g., fibronectin, bone sialoprotein).…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been reported in several different TiO 2 dental implant surfaces in in vitro and in vivo rat tibia studies. 11,[35][36][37][38] The proposed mechanism of titanium-associated osteoinduction is thought to be related to hydroxyl groups and calcium ions present in TiO 2 surfaces. These hydroxyl groups may well promote adsorption of calcium-binding extracellular matrix proteins (e.g., alkaline phosphatase) and RGD-specific peptide sequences (e.g., fibronectin, bone sialoprotein).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, titanium-coated implants were placed in rat tibia, and the microstructure of peri-implant tissue was examined over time. There was maturation of osseointegration at 28 days after implant placement 28) . In our present study, the results suggest that the experimental implant surface showed more enhanced osseointegration than the titanium implant surface, mainly in the trabecular bone region from early after implant placement until completion of osseointegration.…”
Section: Osteocalcinmentioning
confidence: 99%
“…Thin titanium coating was deposited onto the rods using the method of Watazu reported by Okamatsu et al 27) and Morinaga et al 28) . Briefly, thin titanium coating of approximately 100 nm was deposited by a DC/RF sputtering system (L332S-FHS, Anelva, Tokyo, Japan) with a titanium target (99.9% purity, Kojundo Chemical Lab.…”
Section: Experimental Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Micro-CT in implant and periimplant bone research has been popular for the past decade, many authors have studied the implant (Schicho et al, 2007), periimplant bone (Rebaudi et al, 2004;Kim et al, 2008;Yoo et al, 2008;Freilich et al, 2009), interface osseointegration and bone-implant integration with the Micro-CT technique (van Oossterwyck et al, 2000;Sennerby et al, 2001;Butz et al, 2006;Morinaga et al, 2008), and have obtained some meaningful results. From Micro-CT scans, one may determine parameters of periimplant bone like bone volume (BV), bone surface (BS), trabecular thickness (Tb.Th), trabecular separation (Tb.Sp), bone connectivity and bone implant integration etc,.…”
Section: Implant and Periimplant Bonementioning
confidence: 99%